Early‐onset granulomatous arthritis, uveitis and skin rash: characterization of skin involvement in Blau syndrome. (29th October 2019) - Poline, J.; Fogel, O.; Pajot, C.; Miceli‐Richard, C.; Rybojad, M.; Galeotti, C.; Grouteau, E.; Hachulla, E.; Brissaud, P.; Cantagrel, A.; Mazereeuw Hautier, J.; Melki, I.; et al.
Abstract: Background: Blau syndrome (BS) is a rare monogenic autoinflammatory disease caused by NOD2 mutations. BS classically presents in early childhood as a triad of granulomatous polyarthritis, uveitis and skin involvement. Joint and ocular involvement have been characterized by several cohort studies but only very little data are available on skin lesions. Objectives: We aimed to provide a detailed clinical and microscopic analysis of skin manifestations and to study whether they may contribute to an early diagnosis. Methods: We conducted a retrospective multicentre study in a French cohort of 21 patients diagnosed with genetically confirmed BS. Results: Skin involvement was the first clinical manifestation of BS in 15/16 patients with dermatological manifestations. The presence of skin lesions was associated with significant shorter age at diagnosis ( P = 0.03) and diagnostic delay ( P = 0.04). Dermatological assessment allowed an earlier diagnosis ( P = 0.001) and reduces the diagnostic delay ( P = 0.007). Early skin lesions had a homogeneous, stereotypical clinical presentation, namely non‐confluent erythematous or pigmented millimetric papules in 13/14(93%) patients. In contrast, skin lesions occurring during later disease stages had a more heterogeneous clinical presentation, including ichthyosiform dermatosis, panniculitis, livedoid lesions and vasculitis. Whatever their time of occurrence and the clinical aspect, all biopsied showed histologically presence of granuloma. Conclusion: Skin involvement in BS is the earliest clinical manifestation of the BS in the large majority of patients. The recognition of dermatological manifestations as granulomatous skin lesions and early dermatological expertise are the key to an early diagnosis of BS. In view of our results, it seems reasonable to propose a simplified view of skin lesions of BS in which the granuloma is the key structure.